ANALYSIS OF SELF – GRAVITATING PLANETARY SATELLITES IN THE SOLAR SYSTEM - Yasenev, S. O. (Одеські астрономічні публікації, 2016)
As of today there have been more than 180 planetary satellites discovered in the Solar system, and the number of outer moons found continues to grow. Most of those natural satellites have insufficient mass and are able to retain their shape only due to the strength of the electromagnetic force. The purpose of this paper is to analyze the moons’ physical properties. The analysis of planetary satellites as self – gravitating bodies, i.e. celestial bodies which rely on the weight of their own mass and resulting gravitational force to maintain their shape and tend to bring it closer to the hydrostatic equilibrium, was performed.